"A pessoa que se é": sobre as relações entre personalidade e corpo numa sexuação transexualista - Marina Caldas Teixeira (2012)
This thesis looked for elucidate some key aspects of the contemporary phenomenon of transsexualism according to lacanian psychoanalytic approach guidance. The logic of the phenomenon has been discerned, the one hand, around the approach of sexuation lacanian considered as an option of sexual identification (in these terms designated in Seminar 21, 14 May 1974), and on the other hand, considering the lacanian approach of the sinthome. Reflection tried to support its argument based on the analysis of some cases of transsexualism. From this clinical material and testimonies were investigated the circumstances under which the transsexual enjoyment, which ends up leading to sex change surgery and hormones, allows the transsexual to achieve a sort of solution that keeps the person connected to reality, to another, and the body itself. In the end, the study indicated the uniqueness of these cases, noting that the solutions found in each case were subordinated to the occurrence of a contingent event, despite the phallic logic. These solutions are one treatment which reaches resolve the node of personality in those cases.